The impact of catheter-tracking technologies on efficacy and safety in cardiac electrophysiology. (October 2010) - Crystal, Eugene; Shurrab, Mohammed; Lashevsky, Ilan; Crystal, Eli I; Laish-Farkash, Avishag; Newman, David
Usage of nonfluoroscopic mapping systems is increasingly common in invasive cardiac electrophysiology. Novel technologies have resulted in numerous systems potentially leading to improved outcomes of the procedures. Apart from the improvement in procedural outcomes, usage of these systems is associated with a significant reduction in x-ray exposure.